Effectiveness of Earthworms (Eisenia fetida) and Vermicompost Combination in Bioremediation of Oil-Contaminated Soil - Dea Permatasari; Herlina Fitrihidajati (LenteraBio : Berkala Ilmiah Biologi, 2025)
Used oil waste contains toxic substances such as PCBs and PAHs, which are mutagenic and carcinogenic. Illegal disposal into soil without treatment can kill soil microorganisms. This study aims to evaluate the effectiveness of using earthworms (Eisenia fetida) and vermicompost in lowering Total Petroleum Hydrocarbon (TPH) concentrations and enhancing pH, temperature, and moisture conditions in oil-contaminated soil. The research was conducted through an experimental approach employing a Completely Randomized Design (CRD) with a single treatment factor: The experiment included five replicates in 25 treatment units. Parameters measured included TPH levels, pH, temperature, and moisture on day 0, day 18, and day 35. The data were subjected to one-way ANOVA, followed by Duncan’s multiple range test for further comparison. The results showed that all three treatment types effectively reduced TPH levels and optimized pH, temperature, and moisture levels. However, the most effective treatment was the combination of earthworms (Eisenia fetida) and vermicompost, which achieved a TPH reduction of 86.91%, pH ranging from 6.8 to 7.8, temperature ranging from 26.1 to 27.9ºC, and moisture levels between 65.4% to 79.1%. It was concluded that the combination of earthworms (Eisenia fetida) and vermicompost effectively improves the soil quality.